Advances in management accounting. Vol. 16 - Epstein, Marc J.; Lee, John Y. (Advances in management accounting,, 2007)
Advances in Management Accounting (AIMA) publishes well-developed articles on a variety of current topics in management accounting that are relevant to researchers in both practice and academe. As one of the premier management accounting research journals, AIMA is well poised to meet the needs of management accounting scholars. Featured in volume 16 are articles on: Value-Creation Models For Value-Based Management - Review, Analysis, And Research Directions; Performance Standards And Managers Adoption Of Risky Projects; The Effects Of Organizational Culture On Budgetary Conflict - Integrative Versus Distributive Conflict Resolution; The Intervening Effect Of Information Asymmetry On Budget Participation And Segment Slack; Do Accounting Performance Measures Indeed Reduce Managerial Ambiguity Under Uncertainty; Capacity Utilization And The Befcu Model - A Field Study; and, an Application Of The American Productivity And Quality Center Approach To The Evaluation Of Hospital Performance. It also features articles on: The Application Of The Verified Perceptual Bias To Negative Compensation Situations In Management Accounting Research; Activity-Based Cost Management And Manufacturing, Operational And Financial Performance - A Structural Equation Modelling Approach; Team Performance Measurement - A System To Balance Innovation And Empowerment With Control; An Experiment Of Group Association, Firm Performance, And Decision Dissemination Influences On Compensation; and, A Note On The Readability Of Professional Materials For Management Accountants. Researchers in both practice and academe, as well as libraries, would be interested in the articles featured in the AIMA. This book series is available electronically at website.